“their unalienable right and privilege”: New Brunswick’s Challenge to the Militarization of the British Empire, 1807-1814 - Mancke, Elizabeth; Bent, David; Mclaughlin, Mark (Acadiensis, 2017)
Between 1807 and 1814 the New Brunswick Legislative Council and House of Assembly engaged in a protracted struggle with imperial officials over the renewal of militia legislation and, particularly, the constitutionally appropriate balance of power between civil and military authorities. Occurring during the Napoleonic Wars (1803-1815), which engendered an unprecedented militarization of the British world, this struggle demonstrates New Brunswick had a self-consciously assertive colonial government willing to challenge imperial policies that it thought were contrary to the needs of the colony while underscoring the importance of North American settler colonies in maintaining civil government in the empire during those years of war.